A recyclable Amberlyst-15-catalyzed three-component reaction in water to synthesize diarylmethyl sulfones. Issue 21 (18th October 2019) - Kuchukulla, Ratnakar Reddy; Li, Fuhai; He, Ze; Zhou, Lihong; Zeng, Qingle
Abstract : A recyclable Amberlyst-15-catalyzed three-component reaction in water was developed to synthesize asymmetric diarylmethyl sulfones in good to excellent yields with a wide substrate scope. Abstract : A recyclable Amberlyst-15-catalyzed three-component reaction in water was developed to synthesize asymmetric diarylmethyl sulfones in good to excellent yields with a wide substrate scope. Asymmetric diarylmethyl sulfones were prepared via C–C and C–S bond formation in a single step between easily available aryl/alkyl aldehydes, sodium aryl/alkyl sulfinates and tri/dimethoxybenzenes.